The secret life of bees - Kidd, Sue Monk. (London : Headline Review, 2004)
Fourteen-year-old Lily and her companion, Rosaleen, an African-American woman who has cared for Lily since her mother's death ten years earlier, flee their home after Rosaleen is victimized by racist police officers, and find a safe haven in Tiburon, South Carolina at the home of three beekeeping sisters, May, June, and August.
Adult
Keywords: Bee culture -- South Carolina -- Fiction; Racism -- South Carolina -- Fiction; Teenage girls -- South Carolina -- Fiction; Women -- South Carolina -- Fiction; Beekeeping -- Fiction; Girls -- Fiction; Historical fiction; Racism -- South Carolina -- Fiction; Teenagers -- South Carolina -- Fiction; Women -- South Carolina -- Fiction